Thermomechanical Characterisation of Copper Diamond and Benchmarking with the MultiMat Experiment - Marcus Portelli; Michele Pasquali; Federico Carra; Alessandro Bertarelli; Pierluigi Mollicone; Nicholas Sammut; Óscar Sacristán de Frutos; Jorge Guardia Valenzuela; Erich Neubauer; Michael Kitzmantel; David Grech (Shock and Vibration)
The High-Luminosity Large Hadron Collider upgrade at CERN will result in an increase in the energy stored in the circulating particle beams, making it necessary to assess the thermomechanical performance of currently used and newly developed materials for use in beam intercepting devices such as collimators and absorbers. This study describes the thermomechanical characterisation of a novel copper diamond grade selected for use in tertiary collimators of the HL-LHC. The data obtained are used to build an elastoplastic material model and implemented in numerical simulations performed to benchmark experimental data obtained from the recently completed MultiMat experiment conducted at CERN’s HiRadMat facility, where various materials shaped as slender rods were tested under particle beam impact. The analyses focus on the dynamic longitudinal and flexural response of the material, with results showing that the material model is capable of replicating the material behaviour to a satisfactory level in both thermal and structural domains, accurately matching experimental measurements in terms of temperature, frequency content, and amplitude.